Creativity, Activity, Voluntary Work –Activities of Students Participating in the International Baccalaureate Diploma Programme - Kosiorek, Małgorzata; Dobińska, Gabriela (Studia z Teorii Wychowania, 2025)
The article focuses on CAS, (i.e. creativity, activity, service), a subject which constitutes one of the core requirements of the International Baccalaureate Diploma Programme (IB DP). Its specific character and assumptions require skills connected with cognitive engagement, self-development and social activity from the students. This subject matter is overlooked and remains unexplored in pedagogical research. The issues discussed in the article are part of a broader reflection on the reconstruction of the value of the social world of schools implementing the International Baccalaureate Diploma Programme. The empirical material was collected from 6 focus group interviews with students and from participant observation. Using a qualitative research strategy and grounded methodology procedures we reconstructed the ways in which students deal with the completion of CAS. The analysis of the empirical material enabled us to identify three strategies employed alternately by students. This is due to the specificity of the subject, the need to implement the program assumptions, as well as the acquisition of planning and time management skills.